Innovation of Arts and Crafts Teaching Materials Based on Regional Creative Dance Encyclopedia for Grade V Elementary School Students - Hasnanto, Anton Tri; Dzakiri, Anna Fathu; Sodiq, Ahmad (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2024)
Elementary school art and culture education plays an important role in the introduction and preservation of local culture. Often the available teaching materials are less interesting and unable to arouse students' interest. Therefore, it is necessary to develop teaching materials based on regional creative dance encyclopedias in order to develop students' creativity, skills, and understanding of regional cultural heritage. This study aims to determine the development of teaching materials for arts and crafts and the feasibility of teaching materials based on regional creative dance encyclopedias for fifth grade elementary school students. The research method uses research and development by adopting the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of the study were 45 fifth grade elementary school students. Data collection used observation, interviews, questionnaires, and documentation. Data analysis used two analyzes, namely qualitative and quantitative. Qualitative analysis by describing the findings of quantitative data while quantitative analysis is based on the feasibility or validity of the Likert scale. The results of the study showed that based on the average value of the material experts obtained 88.65%, the language experts obtained a percentage of 94.65%, the media experts obtained a percentage of 88.25%, and the teacher's response obtained a percentage of 95.83%. While the small-scale test obtained a percentage of 98.59% and the large-scale test obtained a percentage of 90.47%. From these results, it is concluded that the teaching materials for arts and crafts based on the encyclopedia of regional creative dance for grade V Elementary School students are categorized as very suitable for use in learning activities.